Digital Transformation in Enhancing Leadership Effectiveness at the Makassar City Regional House of Representatives (DPRD) - Sukaini; Riska Dewi; Sulfiana (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the role of digital transformation in enhancing leadership effectiveness at the Regional House of Representatives (DPRD) of Makassar City. The rapid advancement of information technology has encouraged public sector organizations to adapt by implementing digital systems in administrative processes, organizational communication, and public service delivery. This research employed a qualitative method with a descriptive approach. Data were collected through in-depth interviews, direct observation, and document analysis involving leaders and employees of the Makassar City DPRD. Data were analyzed using the Miles and Huberman interactive model, which consists of data reduction, data display, and conclusion drawing and verification. The findings indicate that digital transformation has a positive impact on leadership effectiveness by accelerating organizational communication, strengthening work coordination, improving decision-making processes, and increasing the efficiency of administrative services. Nevertheless, several challenges remain, including limited digital competencies among employees, resistance to organizational change, and inadequate technological infrastructure. The study concludes that the successful implementation of digital transformation requires adaptive leadership, continuous human resource capacity development, and the reinforcement of a technology-oriented organizational culture.